(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
Using polymer and lipid-based drug delivery techniques, the primary objective is to enhance bioavailability, solubility, and dissolution. Studies have proven therapeutic effectiveness, stability, toxicity, and illness detection. This research aims to show how HPLC may be used to measure novel polymer and lipid-based drug delivery systems. As explained in this article, HPLC is one of the most widely used techniques for assessing drug concentration in lipid and polymer formulations under a range of physical conditions. Because HPLC may be used with some detectors and columns, it might be challenging for researchers to find the ideal conditions to develop a simple, sensitive, and repeatable process for their lipid and polymer matrices study. The goal of this review paper is to provide researchers with information on a range of HPLC techniques used in lipid and polymer drug delivery systems.